2008
DOI: 10.1021/jo801754k
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Studies on the Stability and Reactivity of β-Amino Alkylzinc Iodides Derived from Amino Acids

Abstract: Beta-amino alkylzinc iodides are intrinsically unstable toward beta-elimination and protonation. The aim of this study was to determine the rates of these processes and also to understand how the reactivity of a range of beta-amino alkylzinc iodides in Negishi cross-coupling reactions is influenced by the presence of functional groups within the zinc reagent. Decomposition of beta-benzamido alkylzinc iodides occurs by protonation, and the first-order rate constant for the self-protonation of the carbon-zinc bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 24 publications
0
29
0
1
Order By: Relevance
“…The issues include but are not limited to: (1) the spontaneous decomposition of alkyl organometallics via β-elimination or by proto-demetalation,12 (2) the necessity to pre-form the organometallic reagents without purification as they are not air stable, making the use of superstoichiometric (3–4 equiv.) amounts necessary to achieve satisfactory conversions, and (3) often slow transmetalation (vide infra), thereby requiring various additives 13.…”
Section: Introductionmentioning
confidence: 99%
“…The issues include but are not limited to: (1) the spontaneous decomposition of alkyl organometallics via β-elimination or by proto-demetalation,12 (2) the necessity to pre-form the organometallic reagents without purification as they are not air stable, making the use of superstoichiometric (3–4 equiv.) amounts necessary to achieve satisfactory conversions, and (3) often slow transmetalation (vide infra), thereby requiring various additives 13.…”
Section: Introductionmentioning
confidence: 99%
“…The development of cross-coupling strategies to take advantage of halo-amino acid precursors has allowed access to a wide variety of fluorinated unnatural amino acids. Negishi cross-coupling of halo-serine derivatives is a mainstay in this area and was pioneered by the Jackson group [ [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] ]. The Negishi cross-coupling reaction allows two, often readily available, halogen containing building blocks to be coupled together through a halo-zinc intermediate in the presence of palladium.…”
Section: Complex Fluorine-containing Aromatic Amino Acidsmentioning
confidence: 99%
“…Jackson's group built upon the observation that SPhos improved the yields of Negishi cross-couplings. By taking inspiration from their work on the kinetics of β-elimination, the Boc protecting group (see mechanistic studies) 42 was replaced with a trifluoro-acyl (TFA) group (Scheme 10). 43 The TFA protecting group had been shown previously to perturb the alkyl zinc halide from undergoing β-elimination, (see later section on mechanistic studies for further information) so it was hoped that the combination of SPhos and a TFA protecting group on the zinc halide would lead to improved reaction conditions for the synthesis of phenylethylamine derivatives.…”
Section: Synthesis Of Aromatic Amino Acidsmentioning
confidence: 99%
“…87 Jackson and Rilatt further studied this kinetic stability and reactivity of β-amino alkyl zinc iodides in 2008. 88 They found that the N-protecting group on the zinc iodide was critical in determining the rate of β-elimination. Boc protecting groups were found to increase the rate of elimination, and from this it was theorised that the carbonyl group (within the carbamate) was competing with the ester for coordination with zinc, leading to increased elimination.…”
Section: Mechanistic Studiesmentioning
confidence: 99%